Enhancing Learning Outcomes in KPK and FPB through Teaching at the Right Level (TaRL) Using the ‘Musi Board’ in Grade IV Elementary Education - Nilam Permata Sari; Yuli Witanto (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study explores the impact of the Teaching at the Right Level (TaRL) approach, combined with Musi Board media, on enhancing mathematics learning outcomes and student motivation, particularly in the topics of KPK (Least Common Multiple) and FPB (Greatest Common Divisor), among fourth-grade students at SDN Gisikdrono 03, Semarang. A quasi-experimental design with a non-equivalent control group was employed, involving 46 students divided into an experimental group and a control group. Both groups completed pretests and posttests to assess learning gains and motivational changes. The experimental group, which received instruction through the TaRL approach integrated with Musi Board media, demonstrated significantly greater improvements in both learning outcomes and motivation than the control group. Statistical analysis confirmed the effectiveness of the intervention. The findings suggest that applying level-appropriate, interactive, and contextual teaching methods—such as the TaRL approach supported by visual media—can substantially improve student engagement and achievement in elementary mathematics.